A META-ANALYSIS STUDY ON THE ASPECT OF CREATIVITY IN EDUCATION - Wafiq Ali Kasyfi (Study Program Guidance and Counseling, Univesitas Pendidik, 2021)
The success of learning in school is determined by the ability to find and use effective and creative learning strategies. Creativity is not only an important element in solving problems but also an indicator that individuals have higher levels of excellence functions. Creativity character is one of the issues that has not been widely discussed and actualized in the context of education, especially in the focus of creating an effective learning process. A systematic review was used to examine previous research on creativity in the context of education. This study reviewed 10 scientific papers based on the analysis in the study. The results show that creativity has a specific model based on aspects of the definition, characteristics of creative subjects, supporting factors, inhibiting factors, a domain of creativity, and creative strategies in school. Creativity is also a very important character and has a particular model both for students and teachers and for the principals